(untitled) (Research, Society and Development, 2023)
This article consists of an experience report carried out at EMEF Escola Municipal João Nelson dos Prazeres Henriques, in Canaã dos Carajás-PA, in a 6th year class, which developed an interdisciplinary Science and Mathematics Fair project, EUREKA, with the subtheme “Biodegradables in the generation of products as a source of sustainable income”, with the thematic focus on cleaning product: soap for cleaning in general, resulting in soap with the fictitious name SaboEco. The objective was to develop an understanding of the informative pamphlet textual genre and how it is used to disseminate information based on soap production, fulfilling Eureka’s structuring axes: entrepreneurship and sustainability. As methodological procedures, moments of conversation were provided; moments of studying texts in the informative pamphlet genre; cooking oil collection, experimental activity with soap production, textual production and soap exhibition at the EUREKA Fair. Thus, the results were the construction of the informative pamphlet and the production of soap with the reuse of cooking oil.